HEALTHY LIFESTYLE - Shokirova Mohina Erkinovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract : A healthy lifestyle is essential for promoting physical, mental, and social well-being. Modern societies face increasing challenges due to urbanization, sedentary  behaviors,  and  technological  dependence,  which  contribute  to  chronic diseases such as obesity, cardiovascular disorders, and depression. This study explores the role of balanced nutrition, regular physical activity, and mental health practices in enhancing overall human health. Evidence-based interventions and recommendations are  provided  to  support  sustainable  healthy  habits.  The  findings  emphasize  the importance of integrated approaches that combine dietary guidance, exercise routines, and psychological support to improve quality of life and prevent non-communicable diseases.